Welches Wissen nutzen Studierende bei der Planung von Physikunterricht mit digitalen Medien? - Jordans, Melanie; Riese, Josef (Entdecken, lehren und forschen im Schülerlabor. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Bochum 2024)

Planung von Physikunterricht mit sinnvoller Einbettung digitaler Medien: Welches Wissen wird dabei genutzt? - Jordans, Melanie; Riese, Josef (Frühe naturwissenschaftliche Bildung. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Hamburg 2023)

Unterrichtsplanung mit sinnvoller Einbettung digitaler Medien im PU - Jordans, Melanie; Riese, Josef (Lernen, Lehren und Forschen in einer digital geprägten Welt. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Aachen 2022)

How authenticity impacts validity: Developing a model of teacher education assessment and exploring the effects of the digitisation of assessment methods Über Validität und Authentizität: Effekte des Transfers von Testinstrumenten in ein digitales Format auf die erhobenen Aspekte der professionellen Handlungskompetenz - Kulgemeyer, Christoph; Riese, Josef; Vogelsang, Christoph; Buschhüter, David; Borowski, Andreas; Weißbach, Anna; Jordans, Melanie; Reinhold, Peter; Schecker, Horst (Zeitschrift für Erziehungswissenschaft)
Abstract Based on a literature review of studies on teachers’ professional competence and related assessment tools, this paper introduces a model of teacher education assessment. It is influenced by Miller’s (1990) framework of assessment in medical education and includes, among other aspects, performance assessments. This model is used to understand the potential effects of transferring assessment tools into a digital format with assessment feedback. Five examples for such a transfer will be discussed: three methods for various aspects of communication, a test for pedagogical content knowledge, and a test for content knowledge. All five are established instruments well-described in terms of validity. All five have recently been transferred into a digital format. The analysis of this transfer also reveals a potentially harmful effect of digital assessment. The closer an assessment instrument is to assessing action-related parts of professional competence, the more authenticity is required; however, digitisation tends to decrease this authenticity. This suggests that an increasing number of digital assessment tools in teacher education might result in an even more dominant focus on knowledge tests, ignoring other parts of professional competence. This article highlights the role of authenticity in validity and discusses the most suitable assessment format to address various parts of professional competence. It ends by highlighting the lessons learned from the transfer of assessment instruments into a digital format that other academic disciplines might find interesting.
Keywords: Education

Ansätze zur Ermittlung von Kompetenzniveaus im Fachdidaktischen Wissen - Zeller, Jannis; Jordans, Melanie; Riese, Josef (Unsicherheit als Element von naturwissenschaftsbezogenen Bildungsprozessen. Gesellschaft für Didaktik der Chemie und Physik. Online Jahrestagung 2021)

Weiterentwicklung eines physikdidaktischen Tests zum Online-Assessment - Jordans, Melanie; Zeller, Jannis; Große-Heilmann, Rike Isabel; Riese, Josef (Unsicherheit als Element von naturwissenschaftsbezogenen Bildungsprozessen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung virtuell 2021)